2011
DOI: 10.1590/s0103-84782011005000125
|View full text |Cite
|
Sign up to set email alerts
|

Previsibilidade e eficiência no mercado agrícola

Abstract: II Previsibilidade e eficiência no mercado agrícola Predictability and efficiency in agricultural market

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
4

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
(3 reference statements)
1
1
0
4
Order By: Relevance
“…The after crisis series was shown to be predictable with the GMDH model. This research corroborates the work of Righi and Ceretta (2011), who have demonstrated that there is a mild inefficiency for the Brazilian soybean prices series, thus opening the possibility for arbitrage procedures and abnormal returns for this type of investments, as well as opportunities for the farmer to plan how to sell this commodity in moments that are more favourable.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The after crisis series was shown to be predictable with the GMDH model. This research corroborates the work of Righi and Ceretta (2011), who have demonstrated that there is a mild inefficiency for the Brazilian soybean prices series, thus opening the possibility for arbitrage procedures and abnormal returns for this type of investments, as well as opportunities for the farmer to plan how to sell this commodity in moments that are more favourable.…”
Section: Resultssupporting
confidence: 88%
“…Recent studies, such as that of Righi and Ceretta (2011), implementing time series analysis, showed daily quotations for some Brazilian commodities [soybean, cotton (Gossypium hirsutum L.), coffee (Coffea arabica L.) and sweet corn (Zea mays L.)] do not follow anticipated market efficiency, thus generating opportunities arbitrage.…”
Section: Introductionmentioning
confidence: 99%
“…Notam-se evidências discrepantes relacionadas aos mesmos ativos, entre mercados e dependentes dos métodos e dos dados utilizados, conforme apontado por Garcia et al (1988). O único estudo que analisou a eficiência nos mercados agropecuários à vista foi o de Righi & Ceretta (2011), com resultados desfavoráveis à eficiência.…”
Section: Síntese Da Literatura Empíricaunclassified
“…Os autores encontraram que os de razão de variância proveem maior poder que os demais sob passeio aleatório heterocedástico. Os estudos de Bitencourt (2007) e Righi & Ceretta (2011) foram os únicos a utilizarem-nos na inferência sobre a eficiência fraca no mercado futuro de café e nos mercados à vista do algodão, café, milho e soja, respectivamente. Bitencourt (2007) realizou o teste de razão de variância proposto por Lo & MacKinlay (1988) para retornos diários, semanais e mensais.…”
Section: Evidências Empíricas Sobre Eficiência Nos Mercados De Commodunclassified
“…Os estudos sobre os mercados futuros agropecuários são incipientes e pouco explorados metodologicamente (Bitencourt 2007). Bressan & Leite (2001) fizeram-na com testes de correlação serial, Bitencourt (2007) e Righi & Ceretta (2011) testaram sob a abordagem de razão de variância. A hipótese conjunta de não enviesamento e eficiência a preços futuros, sob abordagem de cointegração, foi a metodologia mais empregada nos estudos de derivativos agropecuários brasileiros, realizada por Amado & Carmona (2004), Bitencourt (2007), Duarte et al (2007), Alves et al (2008), Moraes et al (2009), Silva Neto et al (2010 e Fraga & Silva Neto (2011).…”
Section: Introductionunclassified